2001
DOI: 10.1104/pp.125.4.1957
|View full text |Cite
|
Sign up to set email alerts
|

Phytochrome A Mediates Blue Light and UV-A-Dependent Chloroplast Gene Transcription in Green Leaves

Abstract: We characterized the photobiology of light-activated chloroplast transcription and transcript abundance in mature primary leaves by using the following two systems: transplastomic promoter-reporter gene fusions in tobacco (Nicotiana tabacum), and phytochrome (phyA, phyB, and hy2) and cryptochrome (cry1) mutants of Arabidopsis. In both dicots, blue light and UV-A radiation were the major signals that activated total chloroplast and psbA, rbcL, and 16S rrn transcription. In contrast, transcription activities in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 78 publications
0
40
0
Order By: Relevance
“…RNA concentration was determined spectrophotometrically and its integrity was verified using denaturing gel electrophoresis (Chun et al, 2001). For RT-PCR, the RNA was treated with RNase-free DNase (Promega Inc., USA) and used to produce the first-strand cDNA with M-MLV reverse transcriptase (Promega, USA).…”
Section: Methodsmentioning
confidence: 99%
“…RNA concentration was determined spectrophotometrically and its integrity was verified using denaturing gel electrophoresis (Chun et al, 2001). For RT-PCR, the RNA was treated with RNase-free DNase (Promega Inc., USA) and used to produce the first-strand cDNA with M-MLV reverse transcriptase (Promega, USA).…”
Section: Methodsmentioning
confidence: 99%
“…22 Additionally, phyA has been shown to have a role in regulating photoresponses under B illumination. [23][24][25][26][27][28][29][30] The remaining phytochromes, phyB through phyE, contribute to changes in growth and development, primarily in response to R wavelengths. 19,[31][32][33][34][35][36] Notably, spatially localized…”
Section: Tissue-and Isoform-specific Phytochrome Regulation Of Light-mentioning
confidence: 99%
“…15,18,[20][21][22] It has been shown that phyA has additional roles under Bc, including activation of chloroplast transcription in mature leaves under B. 23 Furthermore, it was reported recently that phyA has a major role in the early induction of gene expression for GUN4 and CHLH in Bc light. 24 Results from prior studies demonstrated that 35S::pBVR lines exhibit elongated hypocotyls under Bc light.…”
Section: Spatial-specific Regulation Of Blue-light-dependent Responsementioning
confidence: 99%